PAIR MOTOR COORDINATION ACTION IN SPORTSMEN (ON THE EXAMPLE OF BALLROOM DANCING) - L. V. Kapilevich; Yu. P. Bredikhina (Бюллетень сибирской медицины, 2013)
Learn a special coordinating pair of motor actions in athletes engaged sport ballroom dancing, depending on gender and sportsmanship. The results suggest that beginners dominated coordination, performed individually, while the highly skilled dancers better developed coordination, carried out in pairs. Athletes average individual coordination disturbed by the emergence of sex differences build movements and coordination pair is not formed. The asymmetry of the coordination abilities manifested in the predominance of the deviation from equilibrium (to the right of men and to the left – in women). In this case, the athletes of low and medium level of skill to maintain the leading element of balance and coordination is the visual analyzer, while the skilled dancers defining role goes to the vestibular apparatus.